60 years of IAU symposia. Issue Volume 9:Issue S304(2013) (25th July 2014) - Mickaelian, Areg M.
Abstract : The history of the International Astronomical Union (IAU) meetings goes back to 1922 when the IAU I General Assembly (GA) was held in Rome, Italy, following the IAU creation in 1919. However, until 1953, no individual symposia were organized and GA was the only official gathering for astronomers. Altogether, 8 IAU GA were held during 1922–1952.